Ceratobasidium sp. is associated with cassava witches’ broom disease, a re-emerging threat to cassava cultivation in Southeast Asia - Ana M. Leiva; Juan M. Pardo; Warren Arinaitwe; Jonathan Newby; Pinkham Vongphachanh; Khonesavanh Chittarath; Samoul Oeurn; Le Thi Hang; Alejandra Gil-Ordóñez; Rafael Rodriguez; Wilmer J. Cuellar (Scientific Reports, 2023)
Abstract Cassava witches' broom disease (CWBD) is a devastating disease of cassava in Southeast Asia (SEA), of unknown etiology. Affected plants show reduced internodal length, proliferation of leaves and weakening of stems. This results in poor germination of infected stem cuttings (i.e., planting material) and significant reductions in fresh root yields and starch content, causing economic losses for farmers and processors. Using a metagenomic approach, we identified a fungus belonging to the Ceratobasidium genus, sharing more than 98.3–99.7% nucleotide identity at the Internal Transcribed Spacer (ITS), with Ceratobasidium theobromae a pathogen causing similar symptoms in cacao. Microscopy analysis confirmed the identity of the fungus and specific designed PCR tests readily showed (1) Ceratobasidium sp. of cassava is strongly associated with CWBD symptoms, (2) the fungus is present in diseased samples collected since the first recorded CWBD outbreaks in SEA and (3) the fungus is transmissible by grafting. No phytoplasma sequences were detected in diseased plants. Current disease management efforts include adjustment of quarantine protocols and guarantee the production and distribution of Ceratobasidium-free planting material. Implications of related Ceratobasidium fungi, infecting cassava, and cacao in SEA and in other potential risk areas are discussed.